The effects of concentrated ownership on the performance of the firm: do external shareholdings and board structure matter? - Fauzias Mat Nor,; Faizah Mohd Shariff,; Izani Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The Malaysian corporate governance varies according to the ownership structure of the corporate sector. At one end of the spectrum there are companies in which ownership is dispersed among small shareholders, while control is concentrated in the hands of the large shareholders. This study analyses the role played by concentrated ownerships through the top ten shareholders of the non-financial firms that are listed on the KLSE in determining their performances. A total of 2608 companies are used in this study and various measures of performance and categories of ownerships are used to study the different effect of different ownerships on performance. Ownership roles are observed from two perspectives namely their ownership concentration and the components of this ownership concentration as proxy for corporate governance mechanisms. The finding from this empirical study provides information on the importance of large institutional shareholders in corporate governance. This study also providing evidence that, typically equity owned by the corporations, government, nominees and individuals are directly influencing the financial structures of the firms. This will eventually affect the overall performance of the firms. This indicates that to encourage firm performance, it very much dependent upon the supply of suitable management and directors as well as other stakeholder’s information